Modeling of Dowel Jointed Rigid Airfield Pavement under Thermal Gradients and Dynamic Loads - Ahmed Ebrahim Abu El-Maaty; Ghada Mousa Hekal; Eman Muhammed Salah El-Din (Salehan Institute of Higher Education, 2016)
Concrete pavements have been widely used for constructing runways, taxiways, and apron areas at airports. The aviation industry has responded to increased demand for air travel by developing longer, wider, and heavier aircraft with increasing numbers of wheels to support the aircraft while in ground operation. Many researchers developed their models based on the finite element method (FEM) for the analysis of jointed concrete pavement. Despite the notable improvement, important considerations were overlooked. These simplifications may affect the results of the developed models and make them unrealistic. Sensitivity studies were conducted in this study to investigate the effect of the loading parameters on the load transfer efficiency (LTE) indictors where concept of LTE is fundamental in airfield design procedures. The effect of main gear loading magnitudes in different wheel configurations combined with positive and negative thermal gradients was investigated. The verification process was presented to increases the confidence in the model results. Understanding the response of rigid airfield pavement under such circumstances is important developing a new pavement design procedure, as well as implementing a suitable remedial measure for existing pavements. The results obtained that utilizing a dynamic load allows studying the fatigue cycles that pavement can be subjected under different wheel configurations. Moreover, the change in the thermal gradient from positive to negative significantly changed the slab curvature shape.